PENGARUH AUDIT DELAY, OPINI AUDIT, REPUTASI AUDITOR DAN PERGANTIAN MANAJEMEN PADA VOLUNTARY AUDITOR SWITCHING - Pawitri, Ni Made Puspa; Yadnyana, Ketut (E-Jurnal Akuntansi, 2015)
This research was conducted to re-analyze the influence of audit delay, audit opinion, auditor reputation and management change on voluntary auditor switching. The data used are external secondary data from the annual report of real estate and property companies in 2009-2013 period with a nonparticipant observation methods obtained by accessing the official website of the IDX and ICMD. Based on purposive sampling method, obtained 27 companies sampled. Using logistic regression analysis, this research attempts to examine empirically the influence of audit delay, audit opinion, auditor reputation and management change of voluntary auditor switching. Results of this research show that audit delay, auditor reputation and management change have a significant effect on voluntary auditor switching. The test results also show that the audit opinion has no significant effect on voluntary auditor switching.
Keywords: voluntary auditor switching, audit delay, audit opinion, auditor reputation, management change